The Effect of Video and Leaflets for Health Promotion on Adolescents Knowledge About Early Marriage in Rural Area Indonesia - Nanlohy, Wildia; Andi Asrina; Een Kurnaesih (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2021)
Background: Marriage is mostly carried out by teenagers due to poor knowledge about reproductive health. This issue can lead to dangerous behaviors. Aim: The purpose of this study was to analyze the effect of video education media and leaflets on adolescent knowledge about early marriage in Dobo, Aru Islands. Methods: The research design used was a quasi-experimental approach with a two-group pretest-posttest design approach. The sampling technique in this study was purposive sampling with 98 respondents. Data analysis used SPSS 20.0 and the Paired Samples Test statistical test from independent t-test with a significance level of 95% (α: 0.05) was ran to get the results. Results: The two intervention groups using the Paired Samples Test showed the influence of islands on adolescent knowledge about marriage before using video media from leaflets with p-value <0.05. There was a difference in the effect of knowledge between the video groups of leaflets after the intervention was given using an independent t-test (p value 0.001 < 0.05). Conclusion: There is an influence of the interventions with video and media leaflets. The advantages of leaflet media are clear images that can be seen together, interesting and easy to understand.